Facets of the Polish EU presidency on Greek news websites - Deligiaouri, Anastasia; Katsiola, Martha (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The purpose of this research was to investigate the promotion of the Polish presidency of the European Union through the analysis of three popular Greek news websites. The survey collected articles from the websites, using the keywords Poland and EU presidency, which were published between July 1 and December 31, 2011. Results obtained provide several aspects regarding the presentation of the Polish EU presidency in the Greek media. Additionally, the research results reveal information about the role and activities of the rotating presidency of the European Union, as well as information of the European communicative policy.